2002
DOI: 10.1364/ol.27.001938
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond micromachining of symmetric waveguides at 15 µm by astigmatic beam focusing

Abstract: We report on a new spatial beam-shaping approach for fabrication of waveguides with a circular transverse profile by femtosecond laser pulses, using an astigmatic beam and controlling both beam waist and focal position in the tangential and sagittal planes. We apply this technique to write single-mode active waveguides at 1.5microm in Er:Yb-doped glass substrates. The experimental results are well described by a simple nonlinear absorption model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(86 citation statements)
references
References 12 publications
1
85
0
Order By: Relevance
“…For focused diameters of the order of a few micrometers, this results in a large difference in waveguide sizes in the two directions. This problem can be overcome [58,59] by introducing a focusing geometry in which the femtosecond writing beam is astigmatically shaped by changing both the spot sizes in the tangential and sagittal planes and the relative positions of the beam waists. This shaping allows one to modify the interaction volume in such a way that the waveguide cross section is circular and with arbitrary size.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…For focused diameters of the order of a few micrometers, this results in a large difference in waveguide sizes in the two directions. This problem can be overcome [58,59] by introducing a focusing geometry in which the femtosecond writing beam is astigmatically shaped by changing both the spot sizes in the tangential and sagittal planes and the relative positions of the beam waists. This shaping allows one to modify the interaction volume in such a way that the waveguide cross section is circular and with arbitrary size.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…2) Depending on the level of laser intensity, one can induce any of three qualitatively different types of modification or damage in silica glass: low intensity induces a smooth positive refractive-index change relative to the unprocessed material (type I-fs); intermediate intensity results in birefringent regions (type II-fs); and at high intensity the damage consists of voids embedded into the glass (type III-fs). Type I modification has been used to achieve waveguides and couplers, 1), 3) whereas type III-fs void like defects have been exploited for data storage and photonic crystals. 4), 5) The intermediate type II-fs regime has received little attention until now but indeed seems to have intriguing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, complex structures can be directly written in materials, such as pure silica, that are traditionally challenging for standard direct laser processing. Furthermore, depending on the laser intensity and the material utilized, different features with either positive or negative index change, or voids, can be realized in the bulk of the irradiated material, thus targeting numerous applications such as waveguides, 2 Bragg gratings, 3 diffraction optics, 4 microfluidic channels, 5 and data storage. 6 It has been shown that femtosecond laser writing in wide band gap materials can induce an optically isotropic positive index change 1 as high as 3 ϫ 10 −2 ͑type I_fs͒.…”
mentioning
confidence: 99%